2016
DOI: 10.1667/rr14207.1
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Gold Nanoparticle Radiosensitization on Functionalizing Layer Thickness

Abstract: Gold nanoparticles functionalized with polyethylene glycol of different chain lengths are used to determine the influence of the capping layer thickness on the radiosensitizing effect of the particles. The size variations in organic coating, built up with polyethylene glycol polymers of molecular weight 1-20 kDa, allow an evaluation of the decrease in dose enhancement percentages caused by the gold nanoparticles at different radial distances from their surface. With localized eradication of malignant cells as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 41 publications
3
22
0
Order By: Relevance
“…This is due to the fact that PEG and other similar molecules have densities and effective atomic masses similar to water. The reduction in radiosensitization for thicker coatings agrees with experimental observations . Simulations indicate that a denser coating of shorter PEG chains can achieve similar effects to a sparser coating of longer PEG chains .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is due to the fact that PEG and other similar molecules have densities and effective atomic masses similar to water. The reduction in radiosensitization for thicker coatings agrees with experimental observations . Simulations indicate that a denser coating of shorter PEG chains can achieve similar effects to a sparser coating of longer PEG chains .…”
Section: Discussionsupporting
confidence: 80%
“…The reduction in radiosensitization for thicker coatings agrees with experimental observations. 42 Simulations indicate that a denser coating of shorter PEG chains can achieve similar effects to a sparser coating of longer PEG chains. 43 As both density and length of a molecular coating contribute to its biological effect, a short dense coating offers improved enhancement compared to a longer less dense coating with the same biological effect.…”
Section: B Effect Of Nanoparticle Sizementioning
confidence: 93%
“…Spaas et al recently demonstrated that there was an average loss of 5.2% in radiosensitivity per nanometer of organic capping. 35 In our previous in vitro study, it was concluded that 10 nm PEG-Au-NPs combined to 1.3 MeV protons were more efficient in cell killing than when using lower NP diameter or higher energy protons. 21 This could be explained by the LET profiles shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…The value first decreased with decreasing material density down to %0. 35. Hf-NP absorbed fewer electrons given its lower density and a mean electron energy comparable to heavier metals.…”
Section: A Nanoparticles Of Different Materialsmentioning
confidence: 99%
“…GNPs are the most promising due to their physicochemical properties and high biocompatibility. GNPs absorb the energy of ionizing radiation and also, surface functionalization can dramatically decrease the production of radicals [3].…”
Section: Introductionmentioning
confidence: 99%